1983
DOI: 10.1097/00132582-198303000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Extradural Analgesia Using Bupivacaine and 2-Chloroprocaine on Intervillous Blood Flow During Normal Labour

Abstract: The effect of lumbar extradural analgmig on intervillous blood flow (IBF) during labour was studied in 26 healthy parturients using an i. v. bolus injection of xenon-133. There was a 19% decrease (n.s.) in mean IBF in six parturients (non-extradural control group). Mean IBF increased by 37.5% when 0.25% bupivacaine 10 ml was used and by 35.2% when 2% 2-chloroprocaine 10 ml was used (n.».). When the two extradural groups were combined, the mean difference between IBFi and IBF2 was 45+ 112mlmin"' dl" 1. This inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1984
1984
2009
2009

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The concentrations of local anaesthetics used in this kind of study have, however, been many times higher than those blood concentrations found during clinical use of epidural anaesthesia. The use of different local anaesthetics for epidural analgesia does not seem to influence IBF (20). The use of chloroprocaine and lidocaine in our studies was also evenly distributed between the ephedrine and the control groups (4:5 and 4:5, respectively).…”
Section: Patient Nomentioning
confidence: 41%
“…The concentrations of local anaesthetics used in this kind of study have, however, been many times higher than those blood concentrations found during clinical use of epidural anaesthesia. The use of different local anaesthetics for epidural analgesia does not seem to influence IBF (20). The use of chloroprocaine and lidocaine in our studies was also evenly distributed between the ephedrine and the control groups (4:5 and 4:5, respectively).…”
Section: Patient Nomentioning
confidence: 41%
“…Using the 133 Xe washout method, Jouppila et al (1978) found a slight (but non‐significant) reduction in intervillous blood flow and no change in myometrial blood flow. Using a similar technique, Hollmen et al (1982) studied the effect of epidural analgesia in labour and noticed an increase in intervillous blood flow which they attributed to a decrease in uterine vascular resistance. In animal experiments (Wallis et al 1976), no changes in placental blood flow after epidural anaesthesia were seen, provided blood pressure remained stable.…”
Section: Discussionmentioning
confidence: 99%
“…Conas well as arterial umbilical cord blood CA versely, epidural block is supposed to be benefihave been observed after vaginal delivery, and cial to the fetus since low maternal levels of CA especially in association with fetal acidosis [11, are associated with increased uterine blood flow 18]. [5,9]. In addition, the preserved ability of the fetus to respond to stress during labor after Catecholamine concentrations in venous cord epidural block ought to be a prerequisite for a blood originate mainly from fetus since there normal adaptation after birth.…”
Section: Discussionmentioning
confidence: 99%